(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education is one tool that can be used by a country inthe development of human resources, significantly higher education.Higher education is intended to develop students before they are ready to enter the world of work. One of the essentialcomponents in higher education is lecturers. The success of higher education is determined by lecturers who have high professional commitment. The lecturers’high self-efficacy will be reflected in their work, how the lecturer is responsive to the development of science, and the creation of student well-being. The main objective of the present study was to find out: 1) the direct influence of self-efficacy on the commitment of the lecturer profession; 2) the direct effect of job satisfaction on the commitment of the lecturer profession; 3) the direct effect of self-efficacy on the job satisfaction of lecturers, and 4) the indirect effect of self-efficacy on professional commitment through job satisfaction. The sample is consists of 320 lecturers in South Tangerang City. Path Analysis and SITOREM are used for the analysis of the data. The investigators found that:i) there is a significant positive effect of self-efficacy on professional commitment; (ii) there is a positive influence of job satisfaction on professional commitment; (iii) there is a significant positive effect of self-efficacy on professional commitment through job satisfaction; (iv) there are 14 indicators that become priorities to be repaired immediately and eight indicators that can be maintained and improved.